Method to evaluate the efficiency of manual overhead irrigation in citrus rootstock liner production - CONAN A. SALVADOR; RHUANITO S. FERRAREZI; CARLOS V. G. BARRETO; ROBERTO TESTEZLAF (Engenharia Agrícola, 2016)
ABSTRACT Brazil produces grafted citrus seedlings in closed screen houses to reduce pest and disease incidence. Irrigation is usually performed by hand using either breaker nozzles or drilled polyvinyl chloride (PVC) pipe wands on garden hoses. Rootstocks are produced in cone-shaped containers filled with soilless potting mix. Since the containers have a small upper diameter, nutrient solution capture is reduced with the potential to cause environmental contamination from inefficient fertigation. This study provides a method to assess the efficiency of manual overhead irrigation systems used in liner production. The method consists of determining both the volume of water applied and volume lost (i.e., directly and by percolation) in order to obtain an estimate of the percentage of water loss, irrigation efficiency, and the drainage fraction. The method was tested in a commercial facility under standard production practices. The method’s attributes included simplicity, quick sampling and data collection, and accuracy. The evaluated nursery was found to have low irrigation efficiency (27.14%) and excessive nutrient solution losses (72.86%). Considering an average production of 300,000 liners per year on 20,000 m2, we determined an annual solution loss of 221.8 m3 with an average environmental release of 158.9 kg of fertilizer. Therefore, more efficient irrigation systems are necessary for sustainable citrus rootstock liners production.